Analisis Neraca Air Lahan Gambut pada Kesatuan Hidrologis Gambut Pulau Rupat Provinsi Riau - Kusairi, Muhammad; Sutikno, Sigit; Yusa, Muhamad; Hendri, Andy; Rinaldi, Rinaldi (Seminar Nasional Lahan Suboptimal, 2024)
Kusairi, M., Sutikno, S., Yusa, M., Hendri, A., Rinaldi, R. (2024). Analysis of peatland water balance in the peatland hydrological unit Pulau Rupat, Riau Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 649–658).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Peatlands are the largest place that can be used as water storage. Peatlands consist of 90% water and 10% organic matter, most of which is carbon. With a very large water content, water balance analysis is very appropriate to be used to determine the characteristics of PHU Pulau Rupat. Water balance analysis is a very important analysis to see the condition of the volume of water available spatially and temporally. This study aimed to analyze the condition of the water balance in PHU Pulau Rupat. The analysis is based on the condition of the water balance of each Sub PHU using the MONALAGA water balance model. Based on this method, it was found that PHU Pulau Rupat has two periods of deficit conditions each year. This condition is in accordance with the characteristics of the dry season in Riau Province. The difference between surplus and deficit was -80.46 million m3 in 2014, this condition is in accordance with the presence of 1,216 hotspots in sub PHU-2. The deficit month period that is prone to fires occurs in January to March, then in the period from June to August. Based on these conditions, it can be the basis for water management in controlling peatland fire disasters. So that the level of fire vulnerability in PHU Pulau Rupat can be reduced through collaboration between parties in dealing with deficit months.